Acclimation of branch and leaf hydraulics in adult Fagus sylvatica and Picea abies in a forest through-fall exclusion experiment. (21st November 2017) - Tomasella, Martina; Beikircher, Barbara; Häberle, Karl-Heinz; Hesse, Benjamin; Kallenbach, Christian; Matyssek, Rainer; Mayr, Stefan
Abstract: Decreasing water availability due to climate change poses the question of whether and to what extent tree species are able to hydraulically acclimate and how hydraulic traits of stems and leaves are coordinated under drought. In a through-fall exclusion experiment, hydraulic acclimation was analyzed in a mixed forest stand of Fagus sylvatica L. and Picea abies (L.) Karst. In drought-stressed (TE, through-fall exclusion over 2 years) and control (CO) trees, hydraulic vulnerability was studied in branches as well as in leaves ( F. sylvatica ) and end-twigs ( P. abies, entirely formed during the drought period) sampled at the same height in sun-exposed portions of the tree crown. In addition, relevant xylem anatomical traits and leaf pressure–volume relations were analyzed. The TE trees reached pre-dawn water potentials down to −1.6 MPa. In both species, water potentials at 50% loss of xylem hydraulic conductivity were ~0.4 MPa more negative in TE than in CO branches. Foliage hydraulic vulnerability (expressed as water potential at 50% loss of leaf/end-twig hydraulic conductance) and water potential at turgor loss point were also, respectively, 0.4 and 0.5 MPa lower in TE trees. Minor differences were observed in conduit mean hydraulic diameter and cell wall reinforcement. Our findings indicate significant and fast hydraulic acclimation under relatively mild drought in both tree species. Acclimation was well coordinated between branches and foliage, which might be essential for survival and productivity of mature trees under future drought periods.